Pseudo‐Zn–Air and Zn‐Ion Intercalation Dual Mechanisms to Realize High‐Areal Capacitance and Long‐Life Energy Storage in Aqueous Zn Battery. Issue 34 (28th July 2019) - Wei, Tongye; Li, Qian; Yang, Gongzheng; Wang, Chengxin
Abstract: Aqueous zinc batteries are considered as promising alternatives to lithium ion batteries owing to their low cost and high safety. However, the developments of state‐of‐the‐art zinc‐ion batteries (ZIB) and zinc–air batteries (ZAB) are limited by the unsatisfied capacities and poor cycling stabilities, respectively. It is of significance in utilizing the long‐cycle life of ZIB and high capacity of ZAB to exploit advanced energy storage systems. Herein, a bulk composite of graphene oxide and vanadium oxide (V5 O12 ·6H2 O) as cathode material for aqueous Zn batteries in a mild electrolyte is employed. The battery performance is demonstrated to arise from a combination of the reversible cations insertion/extraction in vanadium oxide and especially the electrochemical redox reactions on the surface functional groups of graphene oxide (named as pseudo‐Zn–air mechanism). Along with adjusting the hydroxyl content on the surface of graphene oxide, the specific capacity is significantly increased from 342 mAh g −1 to a maximum of 496 mAh g −1 at 100 mA g −1 . The surface‐controlled kinetics occurring in the bulk composite ensure a high areal capacity of 10.6 mAh cm −2 at a mass loading of 26.5 mg cm −2, and a capacity retention of 84.7% over 10 000 cycles at a high current density of 10 A g −1 . Abstract : A novel "pseudo‐Zn–air" reaction mechanism in aqueous zinc‐ion batteries is demonstrated, which involves the surface state‐dependent redox reaction and accompanies the formation of a basic zinc salt on the surface of electrode. The zinc‐ion batteries based on this pseudo‐Zn–air and zinc‐ion intercalation dual mechanisms show excellent rate and cyclic performances.